A framework for oceans – lessons in environmental governance. Issue 3 (3rd July 2019) - Shaw, Janette
ABSTRACT: Ocean governance has been portrayed as a challenge since the seas have many resources and valuable environmental features with interested parties across jurisdictions. Different types of ocean governance are recognised worldwide in countries ranging from law-centred practices to planning across set periods of time. Australia coasts and oceans have three layers of government with institutional arrangements across many layers of actors. Trends indicate uncertainty for many listed species, despite improving management in some areas, as reported in the Australian State of the Environment publications. Environmental governance has recently been used as a solution to deal with the scale of environmental problems of oceans and the associated blue economy. Environmental governance has dealt with processes of efficiency, effectiveness, institutional arrangements, social justice and capacity building, but much of this literature focuses on process and lacks an outcome and performance orientation. This paper presents a framework for environmental governance that addressed this lack of outcome and performance orientation. Examining the case study of marine reserves in Victoria, Australian insights are presented that may be significant for future ocean governance.